Islam and Natural Resource Management: The Quranic Perspective - Suhendar, Otong; Febriani, Nur Arfiah (TAJDID, 2024)
The exploitation of natural resources is frequently condemned due to its tendency to inflict environmental harm. This subject requires clarification to prevent misunderstandings. This page provides a description of environmental management from the perspective of the Qur’an, including elucidations of Qur’anic words pertinent to issues, actual practices of environmental stewardship, and principles that should serve as a foundation for engaging with the environment. This article use the theme interpretation technique of the Qur’an to provide a complete description. This article seeks to elucidate how the Qur’an addresses appropriate natural management to mitigate adverse effects and promote sustainability. The study’s findings indicate that the Qur’an permits humanity to engage with nature and its resources, provided it does not result in hazards or adverse effects on the environment.